Long-term renal outcomes in patients with traumatic renal injury after nephrectomy: A nationwide cohort study. (May 2019) - Wang, Shang-Yu; Lin, Kuo-Jen; Chen, Shao-Wei; Cheng, Chi-Tung; Chang, Chih-Hsiang; Wu, Yu-Tung; Liao, Chien-An; Liao, Chien-Hung; Fu, Chih-Yuan; Lin, Jr-Rung; Hsieh, Chi-Hsun
Abstract: Background: The long-term renal outcomes of patients who underwent nephrectomy for traumatic renal injury (TRI) have rarely been reported. Therefore, we investigated the impact of nephrectomy for TRI on long-term renal outcomes. Methods and materials: We extracted data from the National Health Insurance Research Database (NHIRD) of Taiwan from 1999 to 2013 and identified patients with TRI. Adverse kidney outcomes (AKOs), including lifelong dialysis and chronic kidney disease (CKD), were chosen as endpoints of the study. Results: A total of 16, 320 eligible patients were identified in the NHIRD. The incidence of lifelong dialysis was 0.6% (99/15, 789) for patients without nephrectomy, while the incidence was 1.1% (6/531) for nephrectomized patients. Overall, the incidence of AKOs was 2.1% (11/531) in the group that underwent nephrectomy and 1.1% (166/15, 789) in the group without nephrectomy. Before matching, differences in overall AKO incidence between the groups were significant, while propensity score matching eliminated this significance. Conclusions: The results of our study did not indicate that AKOs would occur in patients with TRI who underwent nephrectomy. Highlights: Non-operative management is the mainstream treatment for renal trauma. Emergent nephrectomy for renal trauma will not impose risk of future renal failure. Nephrectomy or not is based on conditions of patients and facility of institute.